(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In this article, we will focus on the study of a system consisting of a wind turbine operating at variable wind speed, an asynchronous machine with dual power supply (DFIG) connected to the network by a stator and supplied by a transducer of the side of the rotor. The conductors are separately controlled for the flow of active and reactive power between the stator (DFIG) and the grid, which is achieved in this article using fuzzy logic and AI-based adaptive control to improve the efficiency of the system and optimize performance to ensure that the active and reactive power reach the required reference values ​​and extract energy. Maximum variable wind speeds (MPPT) and electric current are pumped into the network while maintaining a very good power factor. Our results show that the proposed adaptive controller offers improved power response time, overshoot and stabilization time compared to conventional PI and fuzzy control. The proposed control has been demonstrated by simulation using Matlab / Simulink.